Sanitation work: Realizing equity and inclusion in WASH - Bhakta, Amita; Cawood, Sally; Zaqout, Mariam; Evans, Barbara (Frontiers in Water, 2022)
Recognition of the human right to water, sanitation and hygiene (WASH), and equity and inclusion concerns around gender, disability and age have led to crucial change in WASH programmes and policy, responding to commonly hidden issues such as menstrual hygiene, inclusive facilities for people with disabilities, and affordable services for informal settlements. Despite progress towards realising the rights of end users ‘to’ sanitation, this crucial body of work has overlooked the rights of an unseen, diverse population working ‘in’ these services, including those who handle human waste. There are increasing calls within and beyond WASH for sanitation workers - marginalised by their informal and hazardous roles, and intersections of caste, religion and gender - to realise their rights to safe working conditions and social security. Yet, sanitation work has received little attention from equity and inclusion WASH scholars, despite the pressing need to challenge dominant technical, health-centric framings of sanitation that can overlook workers’ lived realities. We argue for an intersectional, interdisciplinary approach to support sanitation workers to realise rights to fair living and working conditions, including inclusive WASH infrastructure at work. We draw on the limited literature available to highlight gaps in, and show the importance of the sub-sector of equity and inclusion to engage further with the diverse rights of sanitation workers. Increased collaboration between sanitation workers, activists, and allies working on inclusion, labour rights, faecal sludge and solid waste management is paramount to realise sanitation workers’ rights and to truly provide ‘inclusive’ sanitation for all by 2030.